Prevalence, risk factors and outcome of congenital anomalies among neonatal admissions in OGBOMOSO, Nigeria - Akinlabi E. Ajao; Ikeola A. Adeoye (BMC, 2019)
Abstract Background Congenital anomalies (CA) are a major cause of neonatal morbidity and mortality, especially in developing countries. Data on these anomalies are still poorly collated in developing countries. We aimed to assess the prevalence, pattern, risk factors and outcome of congenital anomalies among neonatal admissions in Ogbomoso Town, Nigeria. Methods A cross-sectional retrospective study in which a review of the records of all neonates admitted in the neonatal unit of the Bowen University Teaching Hospital, Ogbomoso over a five-year period (January 2012-December 2016) was undertaken. The occurrence rate and pattern of anomalies were determined, while factors associated with the occurrence and outcome of anomalies were calculated with the odds ratio and 95% confidence interval. Data entry and analysis were performed using SPSS version 21. Results CA were found in 67 of the 1057 neonatal admissions, giving a prevalence rate of 6.3%. Anomalies of the cardiovascular and digestive systems were the most common. A higher proportion of babies referred from other facilities had CA, and this was found statistically significant. There was no significant association between CA and low birth weight, sex, maternal age or parity. The mortality rate among neonates with CA was 10.4%. Although, CA was associated with reduced risk of neonatal mortality compared to those with other acute conditions, this was not statistically significantly. Conclusion CA is a major indication for neonatal admissions in Ogbomoso. There is the need to establish a surveillance system for CA and efforts should be made to raise awareness of the occurrence and risk factors of CA in developing countries.